1991
DOI: 10.1111/j.1399-302x.1991.tb00477.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal bone level and gingival proteinase activity in gnotobiotic rats immunized with Bacteroides gingivalis

Abstract: Bacteroides gingivalis is associated with various forms of periodontal disease. To assess the role of the immune response in modulating B. gingivalis-associated periodontal disease, the effect of immunization of B. gingivalis-induced periodontal bone loss was evaluated in gnotobiotic rats. Male Sprague-Dawley rats immunized with various doses of whole cells or sham-immunized with incomplete Freund's adjuvant were monoinfected with B. gingivalis in carboxymethylcellulose by gavage. Two additional groups served … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 54 publications
2
56
0
Order By: Relevance
“…The bacteria used in this study were P. gingivalis 381, T. denticola ATCC 35404, T. forsythia ATCC 49307, and F. nucleatum ATCC 49256. P. gingivalis strain 381 was chosen due to its known role in alveolar bone resorption in adult periodontitis and its proven ability to colonize the oral cavities of rodents (12,19,21). All bacterial strains were grown under anaerobic conditions (85% N 2 , 10% H 2 , 5% CO 2 ) at 37°C in a Coy anaerobic chamber.…”
Section: Methodsmentioning
confidence: 99%
“…The bacteria used in this study were P. gingivalis 381, T. denticola ATCC 35404, T. forsythia ATCC 49307, and F. nucleatum ATCC 49256. P. gingivalis strain 381 was chosen due to its known role in alveolar bone resorption in adult periodontitis and its proven ability to colonize the oral cavities of rodents (12,19,21). All bacterial strains were grown under anaerobic conditions (85% N 2 , 10% H 2 , 5% CO 2 ) at 37°C in a Coy anaerobic chamber.…”
Section: Methodsmentioning
confidence: 99%
“…They were left overnight in 3% (vol/vol) H 2 O 2 , air dried, and stained for 1 min in an aqueous solution of 0.1% (wt/vol) methylene blue to delineate the cementoenamel junction. The jaws were coded, and an investigator unfamiliar with the code measured horizontal bone loss using the morphometric method of Klausen et al (22,23). Bone loss data were statistically analyzed by a one-way classification analysis of variance with a post hoc Scheffe multiple comparison (M. Norusis, SPSS for Windows: base system user's guide, release 6.0, SPSS Inc., Chicago, Ill., 1993).…”
Section: Methodsmentioning
confidence: 99%
“…Group 4 was left unchallenged. The animals were challenged by inoculation using a 2.5-ml disposable syringe fitted with a 16-gauge gavage tube as described previously (22). A 1-ml sample of the P. gingivalis cell suspension was inoculated into each animal in the following manner: 0.75 ml was gavaged into animals by inserting the tube into the pharynx, 0.2 ml was deposited in the molar gingival area (50 l per quadrant), and 50 l was deposited in the colorectal area.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, this antigen also elicited a potent IgG response, and the animals immunized with P. gingivalis CPS were protected from P. gingivalis-elicited oral bone loss. To date, several P. gingivalis vaccine candidates have been reported to prevent P. gingivaliselicited oral bone loss (8,9,13,18,19,22,28) while other P. gingivalis antigens, such as LPS, do not appear to provide protection from subsequent P. gingivalis infection (5). Unexpectedly, we observed that mice immunized with P. gingivalis CPS develop an IgG response that recognizes P. gingivalis whole organisms.…”
Section: Vol 71 2003 Notes 2285mentioning
confidence: 99%